If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(b + -21) = 41 + -3(b + -4) Reorder the terms: 2(-21 + b) = 41 + -3(b + -4) (-21 * 2 + b * 2) = 41 + -3(b + -4) (-42 + 2b) = 41 + -3(b + -4) Reorder the terms: -42 + 2b = 41 + -3(-4 + b) -42 + 2b = 41 + (-4 * -3 + b * -3) -42 + 2b = 41 + (12 + -3b) Combine like terms: 41 + 12 = 53 -42 + 2b = 53 + -3b Solving -42 + 2b = 53 + -3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3b' to each side of the equation. -42 + 2b + 3b = 53 + -3b + 3b Combine like terms: 2b + 3b = 5b -42 + 5b = 53 + -3b + 3b Combine like terms: -3b + 3b = 0 -42 + 5b = 53 + 0 -42 + 5b = 53 Add '42' to each side of the equation. -42 + 42 + 5b = 53 + 42 Combine like terms: -42 + 42 = 0 0 + 5b = 53 + 42 5b = 53 + 42 Combine like terms: 53 + 42 = 95 5b = 95 Divide each side by '5'. b = 19 Simplifying b = 19
| (3x-7y)(x+3y)= | | 5x-3x-10=-34 | | 3x-8=-5x-20 | | -(v+4)=-4-3v | | -9+k+3k=9-2k | | 14x-21=12x+29 | | 3x+2(x+10)=170 | | N*(2n-4)=17 | | 28x+52=25 | | 3x^2+2x^2=0 | | 2(v+8)=8(-v-8) | | 5+7x=96 | | 7a+2=1 | | 1.5-.4y=3.3 | | 6x^2-44x=-63 | | -(7v+7)=5-4v | | Q+83=902 | | p=6+7p | | -38=2(-43d-24) | | 9c-6-6c=16 | | 4(y+1)=6y-8 | | -10-3h=8h+3+9 | | (4m-120)= | | -8(r-6)=-8-6(-2+5r) | | -13m+7m=18-66 | | 8.7x=156.6 | | 5x-(3x-2)=18 | | -8x-8=3x+25 | | -8-5(1+6x)=5(1-6x)2x | | -3+a/4=-4 | | V+4-8=6(v+7)+2(v+5) | | 8(x-7)=-112 |